Lipase from Candida antarctica (CALB) and cutinase from Humicola insolens act synergistically for PET hydrolysis to terephthalic acid. (August 2017) - Carniel, Adriano; Valoni, Érika; Nicomedes, José; Gomes, Absai da Conceição; Castro, Aline Machado de
Graphical abstract: During PET depolymerization, Humicola insolens cutinase acts mainly for polymer and BHET hydrolysis, whereas Candida antarctica lipase B is predominantly active for BHET and MHET hydrolysis. Highlights: Both enzymes were able to depolymerize PET, especially from Humicola insolens (HiC). CALB is highly efficient to catalyze the release of terephthalic acid (TPA). HiC slowly releases TPA during bis(2-hydroxyethyl terephthalate) hydrolysis. A mixture of HiC and CALB is indicated to improve TPA titer during PET hydrolysis. Abstract: Poly(ethylene terephthalate) (PET) is one of the most important industrial plastics in the world. The development of technologies for its depolymerization aiming at monomer recycling is of paramount interest and in this context enzyme-catalyzed hydrolysis has been recognized as a promising alternative. In the present study, a screening of 10 commercial enzymes using bis-(hydroxyethyl) terephthalate (BHET) as model substrate revealed Candida antarctica lipase B (CALB) and Humicola insolens cutinase (HiC) as potential biocatalysts. HiC showed limitation for the last reaction step, but CALB completely converted BHET to terephthalic acid (TPA), even at the highest substrate concentration investigated (31 mM). When used for PET hydrolysis, HiC demonstrated better potential, although accumulating considerable amounts of the intermediate mono-(hydroxyethyl) terephthalate (MHET). After evaluation of the effects of PET pretreatment, temperature and enzyme addition strategy, the combination of these two enzymes revealed synergy for a more complete PET depolymerization to TPA (mole fraction up to 0.88) and a 7.7–fold increase in PET to TPA yield was achieved. This finding adds new investigation possibilities for one of the most studied and versatile lipases, CALB.